Increasing Students’ Activeness and English Vocabulary Mastery Through Three Phase Technique - Indarti Puji Astuti (Balai Diklat Keagamaan Semarang, 2022)
The research entitled Increasing Activeness and English Vocabulary Mastery through the Application of Three Phase Technique for Class X A3 MAN 3 Sleman, is Classroom Action Research. The purpose of this research is to apply the Three Phase Technique so that it can increase students’ activeness and English vocabulary mastery. This classroom action research was carried out in 2 cycles, each cycle consisting of 3 meetings. This research showed that the activeness of students from the initial conditions, cycle 1 and cycle 2 continued to increase. Percentage of the students’ English mastery who complete and exceed the KKM (from 37,94% to 82,76%). The indicator of the success of a minimum of this Classroom Action Research is, if the percentage of students whose learning scores have reached a minimum of 80%, then it has been successful. The conclusion of this Classroom Action Research is that students’ activeness and English Vocabulary Mastery have increased after learning is applied through the Three Phase Technique.